ENHANCEMENT OF HEAT-RESISTANCE OF PISTON ALLOY AL25 - K. N. Loza; A. A. Mityaev; I. P. Volchok (Литьë и металлургия, 2010)
The control of hardness changing, as well as durability tests of experimental alloys by means of time determination before samples destruction are carried out